Nanoporous platinum grown on nickel foam by facile plasma reduction with enhanced electro-catalytic performance - Zhou, Chunmei (2013)
Template-free growth of nanoporous Pt networks on nickel foam was achieved by room temperature glow discharge plasma reduction. Electrochemical measurements indicated that the obtained porous Pt metallic phase exhibited high electrochemical active surface area with enhanced activity for electro-oxidation of alcohols.